Intelligent cardiovascular disease diagnosis using deep learning enhanced neural network with ant colony optimization - Xia, Biao; Innab, Nisreen; Kandasamy, Venkatachalam; Ahmadian, Ali; Ferrara, Massimiliano (Scientific reports, 2024)
To identify patterns in big medical datasets and use Deep Learning and Machine Learning (ML) to reliably diagnose Cardio Vascular Disease (CVD), researchers are currently delving deeply into these fields. Training on large datasets and producing highly accurate validation results is exceedingly difficult. Furthermore, early and precise diagnosis is necessary due to the increased global prevalence of cardiovascular disease (CVD). However, the increasing complexity of healthcare datasets makes it challenging to detect feature connections and produce precise predictions. To address these issues, the Intelligent Cardiovascular Disease Diagnosis based on Ant Colony Optimisation with Enhanced Deep Learning (ICVD-ACOEDL) model was developed. This model employs feature selection (FS) and hyperparameter optimization to diagnose CVD. Applying a min-max scaler, medical data is first consistently prepared. The key feature that sets ICVD-ACOEDL apart is the use of Ant Colony Optimisation (ACO) to select an optimal feature subset, which in turn helps to upgrade the performance of the ensuring deep learning enhanced neural network (DLENN) classifier. The model reforms the hyperparameters of DLENN for CVD classification using Bayesian optimization. Comprehensive evaluations on benchmark medical datasets show that ICVD-ACOEDL exceeds existing techniques, indicating that it could have a significant impact on CVD diagnosis. The model furnishes a workable way to increase CVD classification efficiency and accuracy in real-world medical situations by incorporating ACO for feature selection, min-max scaling for data pre-processing, and Bayesian optimization for hyperparameter tweaking.
Keywords: Hyperparameter; Bayesian optimisation; Bayes Theorem; Min–max scaler; Bayesova věta; Neural Networks, Computer; Cardiovascular disease; Cardiovascular Diseases; Deep Learning; neuronové sítě; Humans; Ant Colony Optimisation; diagnóza počítačová; Ants; deep learning; Diagnosis, Computer-Assisted; kardiovaskulární nemoci; lidé; Formicidae